2007
DOI: 10.1016/j.drugalcdep.2007.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The impact of illicit drug use and harmful drinking on quality of life among injection drug users at high risk for hepatitis C infection

Abstract: Background-Heavy alcohol use, hepatitis C and illicit drug use each have been shown to have negative impacts on health-related quality of life (HRQL). To date, considerations of HRQL have not played a prominent role in the design and measurement of intervention strategies for out-oftreatment at-risk populations.Methods-Data were collected from out-of-treatment IDUs recruited through street outreach in North Carolina. Multiple linear regression analyses were used to examine the independent effects of HCV status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 49 publications
(45 reference statements)
3
50
1
3
Order By: Relevance
“…33 In a community sample of injection drug users in North Carolina, methamphetamine use had the strongest associations with reduced HRQOL. 35 Our study suggests methamphetamine use is an important contributor to decreased HRQOL in HIVinfected populations, as well.…”
Section: Discussionmentioning
confidence: 62%
“…33 In a community sample of injection drug users in North Carolina, methamphetamine use had the strongest associations with reduced HRQOL. 35 Our study suggests methamphetamine use is an important contributor to decreased HRQOL in HIVinfected populations, as well.…”
Section: Discussionmentioning
confidence: 62%
“…The use of PAS and QL have been discussed in its majority in American studies, showing that within PAS users, lower scores of QL when compared to the general population and with other patients with chronic diseases (4,13) .…”
Section: Resultsmentioning
confidence: 99%
“…intRodUCtion During a long time, the abusive behavior of substances that alter the cerebral functioning causing modifications in the mental state, denominated as psychoactive substances (PAS), was treated with punitive actions for being considered a moral failure or lack of willpower (1) . However, in the last two decades, with the progressive development of scientific studies, the approach started to be done in a preventive and therapeutic way, as it was comprehended as a serious health problem, affecting diverse areas of live of an individual, with direct or indirect repercussions in the quality of life (QL) (2)(3)(4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using QOL instruments with similar populations has informed the choice of instruments in this study. The literature has shown that in and out of treatment IDU return to heavy drug use negatively impacting their QOL (Costenbader, Zule, & Coomes, 2007).…”
Section: Discussionmentioning
confidence: 99%